2017
DOI: 10.1002/cyto.b.21600
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of the Hematoflow™ solution for chronic myelomonocytic leukemia screening

Abstract: We propose a new application of the Hematoflow™ solution that can be used as a flag system for monocytosis management and CMML detection. © 2017 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Recent studies (16,23,24) demonstrated a significant higher percentage of the CD14+/CD16-classical monocyte subset in the peripheral blood of CMML patients (96.6%) than of age-matched healthy subjects (84%) by flow cytometry. Accumulation of CD14+/CD16-monocyte percentage ≥94% could accurately distinguish CMML from other monocytosis with a specificity of 95.1% and a sensitivity of 91.9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies (16,23,24) demonstrated a significant higher percentage of the CD14+/CD16-classical monocyte subset in the peripheral blood of CMML patients (96.6%) than of age-matched healthy subjects (84%) by flow cytometry. Accumulation of CD14+/CD16-monocyte percentage ≥94% could accurately distinguish CMML from other monocytosis with a specificity of 95.1% and a sensitivity of 91.9%.…”
Section: Discussionmentioning
confidence: 99%
“…It could be improved by the use of more specific antibody panels for myeloproliferative/myelodysplastic disorders, specifically, adding progenitor cell markers CD34 and CD117 to every tube and combing HLA‐DR and CD11b with CD4, CD14, and CD64 to more closely follow monocyte maturation. Furthermore, less invasive examination of peripheral blood has shown value based on an increased fraction of CD14+/CD16‐ monocytes, which could be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter can be used as a diagnostic tool. Selimoglu-Buet et al [17] showed that using a cut-off of > 94% classical monocytes, discriminates CMML from reactive monocytosis with a specificity of 95.1% and a sensitivity of 91.9% [17][18][19][20].…”
Section: The Maturing Myelomonocytic Lineagementioning
confidence: 99%
“…It has been shown recently that the accumulation of classical monocytes CD14++CD16− ≥94% in peripheral blood can help to distinguish chronic myelomonocytic leukemia (CMML) from reactive monocytosis . Vazquez et al enumerated classic monocytes by Hematoflow™ solution and found a general overestimation of the genuine classical monocyte percentages comparing to the reference method. However, due to its easy computerization and integration to the middleware, Hematoflow™ solution may be used as a flag system for patients with monocytosis.…”
Section: Automation By Hematological Cytometersmentioning
confidence: 99%